Ring Finger Protein 11 Inhibits Melanocortin 3 and 4 Receptor Signaling - Müller, Anne; Niederstadt, Lars; Jonas, Wenke; Yi, Chun-Xia; Meyer, Franziska; Wiedmer, Petra; Fischer, Jana; Grötzinger, Carsten; Schürmann, Annette; Tschöp, Matthias; Kleinau, Gunnar; Grüters, Annette; et al. (Frontiers in Endocrinology, 2016)
Intact melanocortin signaling via the G protein-coupled receptors (GPCRs) melanocortin receptor 4 (MC4R) and melanocortin receptor 3 (MC3R) is crucial for body weight maintenance. So far, no connection between melanocortin signaling and hypothalamic inflammation has been reported. Using a bimolecular fluorescence complementation library screen, we identified a new interaction partner for these receptors, ring finger protein 11 (RNF11). RNF11 participates in the constitution of the A20 complex that is involved in reduction of tumor necrosis factor F-induced NFB signaling, an important pathway in hypothalamic inflammation. Mice treated with high-fat diet (HFD) for 3 days demonstrated a trend toward an increase in hypothalamic Rnf11 expression, as shown for other inflammatory markers under HFD. Furthermore, Gs-mediated signaling of MC3/4R was demonstrated to be strongly reduced to 20 - 40% by co-expression of RNF11 despite unchanged total receptor expression. Cell surface expression was not affected for MC3R but resulted in a significant reduction of MC4R to 61% by co-expression with RNF11. Mechanisms linking HFD, inflammation, and metabolism remain partially understood. In this study, a new axis between signaling of specific body weight regulating GPCRs and factors involved in hypothalamic inflammation is suggested.